MO147ASSOCIATION OF CHA2DS2-VASC SCORE WITH CAROTID-FEMORAL PULSE WAVE VELOCITY IN CHRONIC KIDNEY DISEASE PATIENTS. (29th May 2021) - Vodošek Hojs, Nina; Ekart, Robert; Bevc, Sebastjan; Piko, Nejc; Hojs, Radovan
Abstract: Background and Aims: Chronic kidney disease (CKD) patients suffer from high cardiovascular morbidity and mortality. Arterial stiffness is an important parameter for the evaluation of cardiovascular risk. Carotid-femoral pulse wave velocity (cfPWV) is the gold standard measure for the assessment of arterial stiffness. CHA2 DS2 -VASc score was originally used to predict cerebral infarction in patients with atrial fibrillation (AF). However, it is also useful in predicting outcome in different cardiovascular conditions, independent of the presence of AF. Therefore, the aim of our research was to assess the association of CHA2 DS2 -VASc score with cfPWV in CKD patients. Method: Eighty-seven non-dialysis CKD patients from our outpatient clinic were included. At the time of inclusion, medical history data and standard blood results were collected, CHA2 DS2 -VASc score was calculated, cfPWV measurements (SphygmoCor System) were done. Correlation between CHA2 DS2 -VASc score and cfPWV was assessed. Multiple regression analysis with cfPWV as dependent and CHA2 DS2 -VASc score, eGFR, urinary albumin/creatinine, haemoglobin, high sensitivity CRP, serum calcium, phosphate and intact PTH as independent variables was performed. Additionally, patients were divided into two groups according to median value of CHA2 DS2 -VASc score (group 1: CHA2 DS2 -VASc score ≤2, group 2: CHA2 DS2 -VASc score >2). Data of both groups were compared by t-test or Mann-Whitney test. Results: CHA2 DS2 -VASc score correlated with cfPWV (r=0.380, p=0.001). In multiple regression analysis only CHA2 DS2 -VASc score was significantly associated with cfPWV (p=0.001). Data of both groups of patients divided according to median value of CHA2 DS2 -VASc score are presented in table 1 . cfPWV was significantly higher in group 2 (13.40±3.50 vs 10.46±2.93, p=0.001). Groups of patients also differed significantly in age, presence of diabetes, eGFR and serum phosphate. Conclusion: CHA2 DS2 -VASc score is associated with cfPWV in CKD patients. Patients with a higher CHA2 DS2 -VASc score have stiffer arteries.